A construção da narrativa do neoconservadorismo católico durante os debates parlamentares de descriminalização do aborto na Argentina (2018-2020) - Angelini, Carla (2023)
After the redemocratization in 1983, the sexual and reproductive rights agenda acquired particular centrality in the Argentine political arena. The Campaña Nacional por el derecho al aborto legal, seguro y gratuito led the construction of a narrative that questioned moralizing conceptions about women's sexuality, historically constructed and legitimized by the Catholic Church. With the gradual recognition of rights, neoconservative actors emerged who tried to prevent these advances in expanding sexual citizenship. This work aims to analyze the construction of the narrative of Catholic neoconservatism during the two parliamentary debates on the decriminalization of abortion (2018-2020) in the country. Anchored in empirical studies of Religious Studies, this research reconstructs the religious arguments that came into play and the strategies for their legitimation, as well as the debates on the laicity of the State when it comes to regulating the lives of all men and women